2011
DOI: 10.1007/s00405-011-1543-9
|View full text |Cite
|
Sign up to set email alerts
|

Does laryngopharyngeal reflux cause intraoral burning sensations? A preliminary study

Abstract: Intraoral burning sensations are a common problem in the otolaryngological practice. The aim of this study was to evaluate if laryngopharyngeal reflux can cause intraoral burning sensations by measuring oropharyngeal acid reflux. Patients with recurring intraoral burning sensations underwent oropharyngeal pH monitoring in our outpatient clinic. The pH catheter was placed at the level of the uvula. The catheter contained an externally worn transmitter, which wirelessly sent the data to a monitor. In addition, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
(43 reference statements)
1
13
0
1
Order By: Relevance
“…3 In the same way, Becker et al observed that 50% of patients suffering from recurring intraoral burning sensations had pharyngeal reflux events at the oropharyngeal pH measurement. 14 However, these authors did not conclude a potential association between both conditions because they did not observe temporally significant association between reflux events and the symptom occurrence. 14 In the majority of these studies, the patient inclusion criteria were based on GERD diagnosis criteria, which yield the comparison of our results with limited studies in the literature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…3 In the same way, Becker et al observed that 50% of patients suffering from recurring intraoral burning sensations had pharyngeal reflux events at the oropharyngeal pH measurement. 14 However, these authors did not conclude a potential association between both conditions because they did not observe temporally significant association between reflux events and the symptom occurrence. 14 In the majority of these studies, the patient inclusion criteria were based on GERD diagnosis criteria, which yield the comparison of our results with limited studies in the literature.…”
Section: Discussionmentioning
confidence: 92%
“…14 However, these authors did not conclude a potential association between both conditions because they did not observe temporally significant association between reflux events and the symptom occurrence. 14 In the majority of these studies, the patient inclusion criteria were based on GERD diagnosis criteria, which yield the comparison of our results with limited studies in the literature. Only Becker et al based the diagnosis of reflux on pharyngeal events through an oropharyngeal device that exhibits different sensitivity and specificity from HEMII-pH.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 Si bien el uso de los inhibidores de la bomba de protones en pacientes con SBU y RGE ha aumentado, puede que no sea necesariamente beneficioso; Becker et al no observaron conexión causal entre reflujo y sensación de ardor intraoral en una serie de 11 pacientes estudiados con ambas patologías. 20 Estudio salival: Una de las quejas más frecuentemente asociadas al SBU es la xerostomía, debido a esto, las alteraciones en el flujo salival como causa de SBU secundario deben ser descartadas mediante pruebas de sialometría no estimulada. 21 Estudio hormonal: en un estudio sobre mujeres con menopausia y molestias orales, Volpe et al encontraron que, con la suplementación de estrógenos, mejoraron los síntomas objetivos y subjetivos en 12 de 22 pacientes tratadas con estriol, y 7 de 10 pacientes tratadas con estrógenos conjugados asociados a noretisterona, por lo que las mujeres con receptores de estrógenos en la mucosa oral, pudieran disminuir la sintomatología con terapia de reemplazo hormonal, no pudiendo garantizarse que sea un tratamiento efectivo.…”
Section: Introductionunclassified
“…The lack of a correlation between laryngopharyngeal reflux and BMS has led to the conclusion that the prescription of omeprazole should be revised due to this drug's side effects and the modest benefits in using it to treat the condition 81 …”
Section: Systemic Diseases With Oral Manifestationsmentioning
confidence: 99%